Melacak Akar Persoalan Bias Gender dalam Penafsiran Al-Qurâan dan Hadis (Metode dan Pendekatan Pemikiran Fatima Mernissi tentang Feminisme) - Badrian, Badrian (IAIN Antasari Banjarmasin, 2013)
Religion is often regarded as the cause of gender inequality permission, or at least, the interpretations of the teachings of religion have been rated to put women in the position of marginal and malesâ subordinate. The main concern is whether gender inequality in the religion derived from the nature of religion itself or whether it comes from the comprehension, interpretation and religious idea which may be influenced by tradition and culture or other influencing factors. The reaction to inequality and injustice against women is what led to the emergence of the feminist movement among Muslim scholars, such as Fatima Mernissi. According to Mernissi, oppression and discrimination against women in the Muslim community, is not the nature of the religion, or as Mernissi defines it with the term Islamic Treatise, because it opposes the universal doctrine, namely justice and the equality of men and women. The women marginalization is more caused by a political system, including ideological, legal, and social culture. The system of patriarchal ideology and the interests of the political elite, which Mernissi termed by political Islam, that distorts the Islamic Treatise.